2023
DOI: 10.1186/s13052-023-01504-w
|View full text |Cite
|
Sign up to set email alerts
|

Associations between basic motor competencies and physical fitness in Spanish pre-schoolers: a cross-sectional study

Gaizka Legarra-Gorgoñon,
Yesenia García-Alonso,
Robinson Ramírez-Vélez
et al.

Abstract: Background Basic motor competencies (BMC) play a vital role in child development and are a primary focus of physical education. However, there is a lack of research on BMC in preschool-aged children, making this study particularly significant. The present study aims to examine the relationship between BMC and physical fitness components in Spanish preschool children. Methods This cross-sectional study was conducted on 101 children (n = 52 boys, ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The descriptive values obtained in PF are similar to those of the preschool population in Chile [14][15][16][17], but lower than those reported in other countries [42][43][44]. This situation could be explained by the long length of the Chilean school day, which leads to low energy expenditure [63,64], low levels of physical activity [18], high levels of overweight and obesity [65], as a result of poor nutrition [17,65,66].…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…The descriptive values obtained in PF are similar to those of the preschool population in Chile [14][15][16][17], but lower than those reported in other countries [42][43][44]. This situation could be explained by the long length of the Chilean school day, which leads to low energy expenditure [63,64], low levels of physical activity [18], high levels of overweight and obesity [65], as a result of poor nutrition [17,65,66].…”
Section: Discussionsupporting
confidence: 69%
“…Regarding the correlations between BMI and the different components of physical fitness in boys and girls, studies deliver similar results, showing that higher levels of GMC correlate with better fitness in both boys and girls [20,43,52,78]. However, the results of the correlations between GMC and BMI were lower compared to a study conducted in South Africa [43], which only found an inverse correlation with cardiorespiratory fitness (r= −0.127), a situation that could be due to factors such as the level of physical activity and sociodemographic, environmental and nutritional factors, among others.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations